Molecular and Growth Responses of Musa acuminata var. Barangan Post Application of Beneficial Endophytic Bacteria - Hanifah Yusadi; Arief Pambudi; Yunus Effendi (Institut Pertanian Bogor, 2025)
Endophytic bacteria reside in plants' roots and can benefit plant growth. The study aimed to evaluate the application of an endophytic bacterial consortium in enhancing the growth of banana plants and identify genes that maximally assist in nutrient utilization during banana plant growth. One-month-old banana plants were inoculated by soaking them for one hour in a 500 mL suspension of endophytic bacteria. In vivo observations were conducted in the greenhouse at Al-Azhar University Indonesia over 40 days, during which morphological and physiological growth were calculated. The results revealed that control plants exhibited lower growth than those treated with endophytic bacteria. The application of endophytic bacteria led to increased growth in banana barangan plants, as evidenced by improvements in leaf length, leaf width, plant height, and chlorophyll levels. Furthermore, a semi-quantitative analysis of banana plants treated with Cytobacillus depressus, Bacillus stratophericus, and B. mycoides revealed genes significantly contributing to growth. These genes, including WRKY33, Ma03_92660, Ma01_901890, Ma04_936790, and Pho-1,2, exhibited their highest expression levels starting from the 28th day of the experiment. Keywords: plant growth, endophytic consortium bacteria, semi-quantitative real-time PCR, identify genes